THE ISSUE OF CULTURAL DIVERSITY AND TOLERANCE IN MODERN GEORGIAN POLITICS - Darchashvili, Manana (Journal of Education Culture and Society, 2020)
Aim. Georgia has traditionally been a country of cultural diversity. Due to the proper political approach, Georgian authorities of all times have managed to successfully govern the peaceful coexistence of people of different nationalities and religions. It is true that in the post-Soviet period, there was some disagreement between the cultures inspired by external forces; however, generally, all the authorities made every effort to legally strengthen the inherited tolerant habit. The paper does not deal with the conflicts of ethnopolitical nature, staged by Russia. The mentioned issue is a part of the country’s domestic policy, which is important and still is relevant nowadays, therefore the paper aims to study the role of cultural diversity and tolerance in modern Georgian politics, the attitude to it, and how the country managed to preserve the centuries-old heritage. Methods. Based on several empirical materials, various researched-studied documents, scientific papers, analysis of government documents, the use of the method of historicism is presented in the paper. Results. The paper presents the current existing reality in Georgia in the field of cultural diversity and the effective steps of the state for the proper development of cultural diversity. Conclusion. Modern Georgian politics is motivated to involve ethnic and religious minorities in the process of monitoring and implementing the Culture Policy Action Plan, based on the recent history and new current worldwide tendency, which will guarantee the establishment of a tolerant society and democracy in Georgia.